2020
DOI: 10.3758/s13428-020-01452-x
|View full text |Cite
|
Sign up to set email alerts
|

The Free-movement pattern Y-maze: A cross-species measure of working memory and executive function

Abstract: Numerous neurodegenerative and psychiatric disorders are associated with deficits in executive functions such as working memory and cognitive flexibility. Progress in developing effective treatments for disorders may benefit from targeting these cognitive impairments, the success of which is predicated on the development of animal models with validated behavioural assays. Zebrafish offer a promising model for studying complex brain disorders, but tasks assessing executive function are lacking. The Free-movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(126 citation statements)
references
References 109 publications
(128 reference statements)
8
113
1
Order By: Relevance
“…Recording percentage-use of reoccurring patterns of four consecutive turn choices, known as tetragrams, over one hour of exploration gives rise to a 'global' search strategy. Similar exploration strategies, predominantly reliant on alternations, have been reported in rodents, both in the FMP Y-maze and T-maze using the same analysis (Cleal et al, 2020;Gross et al, 2011). Behavioural assessment of one hour of free exploration in the FMP Y-maze enables the identification of working memory abilities and cognitive flexibility, presenting the FMP Y-maze as a useful tool for assessing memory processing in animal models and potentially patients with disorders characterised by cognitive decline.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Recording percentage-use of reoccurring patterns of four consecutive turn choices, known as tetragrams, over one hour of exploration gives rise to a 'global' search strategy. Similar exploration strategies, predominantly reliant on alternations, have been reported in rodents, both in the FMP Y-maze and T-maze using the same analysis (Cleal et al, 2020;Gross et al, 2011). Behavioural assessment of one hour of free exploration in the FMP Y-maze enables the identification of working memory abilities and cognitive flexibility, presenting the FMP Y-maze as a useful tool for assessing memory processing in animal models and potentially patients with disorders characterised by cognitive decline.…”
Section: Introductionsupporting
confidence: 60%
“…All other sequences were used at a level equivalent to chance selection. Prior wsork from our group has demonstrated that changes in global spatial activity patterns, particularly those relating to alternations and repetitions, are representative of changes in working memory processing (Cleal, et al, 2020). Previous work has also demonstrated similar patterns of alternations in young adult zebrafish ranging from 3-6-months old (Cleal & Parker, 2018;Fontana, Cleal, Clay, et al, 2019).…”
Section: Changes In Working Memory In Healthy Aging Zebrafishmentioning
confidence: 79%
See 1 more Smart Citation
“…Here, we aimed to establish whether young-adult zebrafish develop cognitive or psychomotor sensitization to repeated administrations of AMPH and NIC, as assessed through the impact on working memory, locomotor activity, and cognitive flexibility. To do this, we used an established behavioral assay for zebrafish that has high translational relevance to humans, the FMP Y-maze (Cleal et al 2020). We assessed locomotor activity, working memory, and behavioral flexibility at four time points: baseline (prior to any drug exposure), chronic exposure (14 days of drug exposure), withdrawal (2 days without drug), and finally following drug challenge (single, repeat drug exposure).…”
Section: Introductionmentioning
confidence: 99%
“…Y-maze setups allowing free movement are common in rodent studies to measure spatial working memory and exploratory behaviour (Kraeuter, Guest and Sarnyai, 2019) . Miniature single fly Y-mazes have been used in flies for the same purpose (Buchanan, Kain and de Bivort, 2015;Lewis et al , 2017;Cleal et al , 2020) . Y-mazes have also been used for naive and learned odour preferences in insects other than flies (Dupuy et al , 2006;Carcaud et al , 2009;Josens, Eschbach and Giurfa, 2009) .…”
Section: Y-maze Designs For Olfactory Behavioursmentioning
confidence: 99%